The secret kingdom - Nimmo, Jenny (London : Egmont UK, 2011)
"Timoken has to flee his secret forest kingdom after it is attacked by sneaky, shape-shifting viridees. Protected from birth by a magical moon spider web, he travels with his camel, Gabar, seeking a new kingdom - a new home. Timoken also has magic himself. He can conjure rain from the air, talk to animals and fly high in the air. And when he saves three leopard cubs from a hunter, they become enchanted too, and sworn to protect him. But the powerful, slimy green viridees are always just a breath behind him. They want the moon spider's web. And they will do anything to get it..." --From the publisher.
JF/FAN ak
Keywords: Magic -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Camels -- Juvenile fiction; Fantasy fiction, Juvenile